ANALISIS FASILITAS EKONOMI AKIBAT PEMEKARAN WILAYAH DI KABUPATEN TULANG BAWANG BARAT - , SELVIANTI YUSNITASARI, Drs. Risyanto, M.S dan Dr. Lutfhi Muta'ali, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Tulang Bawang Region is new district which be created by region development. The aim from region growing is to increase public service in new otonom area, include economic facilities. Economic facilities who be studied such market, bank, cooperation, stall, and food stall. The aim of this research are identify economic facilities region Tulang Bawang Barat after created growing, identify serviceability of economic facilities in Tulang Bawang Barat district, determine the right economic facility location to fill up serviceability for people needs. The research is mixed method. The method for quantitative is paired sample t test, while for qualitative method use interview technique, which for government and trader use key person technique. For consumer, are used accidental method in Tulang Bawang Tengah, Tumijajar, and Lambu Kimbang. From this research, The government in develop economic facilities are still focus on easiness of licensing procedure, facilities revitalization which still lacking, like market and cooperation. Cooperation was the only one facilities who be influence by region growing. It's can be explained from value of sig 2 tailed which show 0,43. The development lead to city more than rural urban. It's happen too in range of good in every facilities, but on threshold serviceability, the developing more lead on facilities in village region. From the existing of facilities population distribution and serviceability value, the location determination is more leaded on village region. It's aim to reduce disparity in city and village region.